Contactless transient carrier spectroscopy and imaging technique using lock-in free carrier emission and absorption - Fiacre E. Rougieux (Nature Portfolio, 2019)
Abstract In this paper we present a contactless transient carrier spectroscopy and imaging technique for traps in silicon. At each pixel, we fit the transient decay of the trap emission which allows us to obtain both the trap time constant and trap concentration. Here we show that this technique allows for high-resolution images. Furthermore, this technique also allows to discriminate between the presence of thermal donors or oxygen precipitates in as-grown wafers, without requiring a thermal donor killing step.